2023
DOI: 10.1063/5.0130817
|View full text |Cite
|
Sign up to set email alerts
|

Modular mixing in plasmonic metal oxide nanocrystal gels with thermoreversible links

Abstract: Gelation offers a powerful strategy to assemble plasmonic nanocrystal networks incorporating both the distinctive optical properties of constituent building blocks and customizable collective properties. Beyond what a single-component assembly can offer, the characteristics of nanocrystal networks can be tuned in a broader range when two or more components are intimately combined. Here, we demonstrate mixed nanocrystal gel networks using thermoresponsive metal–terpyridine links that enable rapid gel assembly a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 70 publications
0
33
1
Order By: Relevance
“…Computation-guided design of disordered structures with desired optical properties is particularly compelling for soft hybrid materials (e.g., plasmonic gels) , that can dynamically reconfiguremodulating how they interact with lightin response to stimuli. Recently, MPM has been applied to compute the optical properties of such linked nanocrystal gel networks, including under strain . MPM can readily model hybrid materials comprising both dielectric (e.g., semiconductor) and metal nanoparticles or with hierarchical nanoparticle ordering, significantly expanding the design space where computation can enhance experimental discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Computation-guided design of disordered structures with desired optical properties is particularly compelling for soft hybrid materials (e.g., plasmonic gels) , that can dynamically reconfiguremodulating how they interact with lightin response to stimuli. Recently, MPM has been applied to compute the optical properties of such linked nanocrystal gel networks, including under strain . MPM can readily model hybrid materials comprising both dielectric (e.g., semiconductor) and metal nanoparticles or with hierarchical nanoparticle ordering, significantly expanding the design space where computation can enhance experimental discovery.…”
Section: Discussionmentioning
confidence: 99%
“…The mixing trends in the extinction spectra and effective dielectric response were successfully reproduced in simulations using a mutual polarization method (MPM) that we recently developed to efficiently compute the optical response of structurally and compositionally complex nanoparticle assemblies (Figure c and Figures S4 and S5). In fact, the predicted resonances in the dielectric functions were useful to guide and ultimately improve the quality of the fits to the IR-VASE data, especially for doped metasurfaces, the optical responses of which were more spectrally complex. We define the metamaterial’s effective dielectric response ε eff (ω) through the relation ⟨ D ⟩ = ε eff ·⟨ E ⟩, where ⟨ E ⟩ and ⟨ D ⟩ are the average electric field and electric displacement throughout the metamaterial, respectively (see details in the Supporting Information).…”
mentioning
confidence: 99%
“…To facilitate thermoreversible nanocrystal gelation, oleate-capped ITO nanocrystals (oleate-ITO) were subjected to direct ligand exchange with TLs , consisting of a terpyridine terminal domain, a solubilizing polyethylene oxide-like backbone, and a tricarboxylate anchor for binding to the nanocrystal surface (Figure a). The ligands were synthesized using established protocols , with a modification to vary the number of polyethylene oxide units in the ligand backbone, enabling manipulation of its length (Figures S1–S3 in the Supporting Information). The Fourier transform infrared spectroscopy (FTIR) of TL -ITO shows characteristic peaks of TL in the fingerprint region, with the absence of the ν­(CO) peak at 1726 cm –1 observed in TL , indicating that TL is attached to the nanocrystal surface via the tricarboxylate domain (Figure S6 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…17,19−23 In contrast to close-packed nanocrystal assemblies, 24,25 nanocrystal gels can incorporate nanocrystals with different compositions and without specific size or shape constraints, enabling the emergence of collective properties from diverse building blocks. 26,27 Discrete, disordered assemblies of nanoparticles, like clusters and strings, have been shown to exhibit a collective plasmonic response that varies with their structural attributes, 28−33 yet their spectra could be only qualitatively compared to simulations, because of structural heterogeneity. 34,35 In our own recent work, we showed that thermoreversible metal-coordination links 36,37 result in reproducible structures and consistent assemblyinduced optical changes in single-component and multicomponent gel networks of ITO nanocrystals, but we lacked a mechanism to systematically tune gel structures and the resulting optical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation